2021
DOI: 10.1039/d1nj03941e
|View full text |Cite
|
Sign up to set email alerts
|

The charge transfer effect on SERS in a gold-decorated surface defect anatase nanosheet/methylene blue (MB) system

Abstract: Revealing substrate−molecule vibronic coupling enhancement, especially photoinduced charge transfer (CT) process, is hugely important for understanding Surface-enhanced Raman spectroscopy (SERS) enhancement mechanism. In this work, oxygen atoms were extracted from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…The main Raman peaks of MB powder are located at 448, 505, 594, 773, 1184, 1400, 1502, and 1624 cm –1 (Figure b). These results are consistent with literature reports. , The detailed Raman vibrational assignments of MB molecules are displayed in Table S1.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The main Raman peaks of MB powder are located at 448, 505, 594, 773, 1184, 1400, 1502, and 1624 cm –1 (Figure b). These results are consistent with literature reports. , The detailed Raman vibrational assignments of MB molecules are displayed in Table S1.…”
Section: Resultssupporting
confidence: 92%
“…These results are consistent with literature reports. 48,49 The detailed Raman vibrational assignments of MB molecules are displayed in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman signals observed at 891, 1155, 1182, 1300, 1393, 1434, 1504, and 1622 cm −1 are the typical vibrational modes of MB (Table S2, Supporting Information), in agreement with previous reports. [32][33][34] To fabricate a plasmonic substrate under excitation with a laser wavelength of 633 nm, we deposited gold layers of different thicknesses to prepare various CGA substrates, and investigated their SERS performances in the detection of 10 −7 m MB. Figure 3c shows that the intensity of the SERS signals increased when the thickness of the gold layer was increased from 10 to 30 nm, and then declined after further increasing the thickness from 30 to 90 nm.…”
Section: Evaluation Of Sers Performancementioning
confidence: 99%
“…For each APM analyte, the varied EF and ER values reflect the degree of CT fluctuation at different vibrational modes . The variations in molecular and electronic structure caused by CT can be analyzed using Raman peak shapes and vibrational frequencies.…”
mentioning
confidence: 99%
“…For each APM analyte, the varied EF and ER values reflect the degree of CT fluctuation at different vibrational modes. 35 The variations in molecular and electronic structure caused by CT can be analyzed using Raman peak shapes and vibrational frequencies. The results of spectroscopic analysis (Figure S14) revealed that the aromatic −CH and −N(H)R (R = H or alkyl) groups in APM compounds were complexed with POE through hydrogen bonds (H-bond).…”
mentioning
confidence: 99%